Tanggung Jawab Guru Pendidikan Agama Kristen dalam Meningkatkan Kualitas Proses Pembelajaran Peserta Didik - Zai, Odaligo (Pusat Riset dan Inovasi Nasional, 2024)
This study comprehensively examines the responsibilities of Christian Religious Education (PAK) teachers in improving the quality of student learning, encompassing academic, character, faith, and spiritual aspects. Christian Religious Education (PAK) teachers function not only as instructors delivering subject matter but also as educators, mentors, and role models of Christian life, bearing moral and spiritual responsibilities in shaping students' personalities. The role of Christian Religious Education (PAK) teachers is highly strategic, as they play a vital role in instilling faith values, building learning motivation, and shaping students' character with integrity. This study employed a qualitative descriptive approach with purposeful sampling, involving Christian Religious Education (PAK) teachers with at least five years of teaching experience to ensure the depth of the data obtained. Data were collected through classroom observations, portfolio documentation, teacher reflections, and open-ended questionnaires to obtain a realistic picture of teaching practices. Analysis was conducted descriptively to highlight the phenomena occurring in the field. The results indicate that the responsibilities of Christian Religious Education (PAK) teachers include sistem lesson planning, setting clear objectives, selecting appropriate teaching methods, providing positive motivation, building harmonious relationships between teachers and students, and serving as role models consistent with the teachings of Christ. Catholic Religious Education teachers who emulate Jesus' method, prioritizing love, integrity, rationality, and creativity, are able to create an effective, enjoyable, and meaningful learning environment, both academically and spiritually. These findings confirm that the quality of Catholic Religious Education teachers directly influences students' motivation, academic achievement, character, and faith development. Therefore, the responsibility of Catholic Religious Education teachers extends beyond the transfer of knowledge to fostering faith, morals, ethics, and spirituality, which are the primary foundations of holistic education based on Christian values.